Genome-wide analysis of the Hsp70 family genes in pepper (Capsicum annuum L.) and functional identification of CaHsp70-2 involvement in heat stress. (November 2016) - Guo, Meng; Liu, Jin-Hong; Ma, Xiao; Zhai, Yu-Fei; Gong, Zhen-Hui; Lu, Ming-Hui
Highlights: A total of 21 CaHsp70 genes were identified in pepper. The conserved CaHsp70 domain, motif compositions and cis -acting elements in promoters were analyzed. The expression of all of the CaHsp70 genes was analyzed in different organs and heat stress. The thermotolerance of Arabidopsis overexpressing CaHsp70-2 was analyzed. Abstract: Hsp70s function as molecular chaperones and are encoded by a multi-gene family whose members play a crucial role in plant response to stress conditions, and in plant growth and development. Pepper ( Capsicum annuum L.) is an important vegetable crop whose genome has been sequenced. Nonetheless, no overall analysis of the Hsp70 gene family is reported in this crop plant to date. To assess the functionality of Capsicum annuum Hsp70 ( CaHsp70 ) genes, pepper genome database was analyzed in this research. A total of 21 CaHsp70 genes were identified and their characteristics were also described. The promoter and transcript expression analysis revealed that CaHsp70s were involved in pepper growth and development, and heat stress response. Ectopic expression of a cytosolic gene, CaHsp70-2, regulated expression of stress-related genes and conferred increased thermotolerance in transgenic Arabidopsis . Taken together, our results provide the basis for further studied to dissect CaHsp70s' function in response to heat stress as well as other environmental stresses.